Challenges of Strategic Planning in Welfare Organization - Ali Mohammad Mosadeghrad; Ahmad Fayaz-Bakhsh; Fataneh Amini (Tehran University of Medical Sciences, 2018)
Background and Aim: Strategic planning has an important role in achieving competitive advantage for nonprofit organizations. However, some strategic plans fail. The present study aimed to investigate challenges of strategic planning in Welfare Organization. Materials and Methods: A qualitative approach was used for this case study. In-depth semi-structured interviews were conducted with 12 senior and middle managers who were members of the strategic planning committee. Content analysis method was used for data analysis, and 7 themes and 16 sub-themes were identified from the data. Results: Lack of justification of the strategic planning, the strategic planning model, inappropriate composition of the strategic planning team, the structural and managerial changes of the Welfare Organization, time limitation, insufficient training, and budget constraints were the main challenges of strategic planning in the Welfare Organization.  Conclusion: If the strategic planning challenges are not managed well, more problems are expected to occure during the implementation of the strategic plan. Senior managers' commitment, strong management and leadership, participative corporate culture, education and training, staff empowerment, and provision of required resources will facilitate strategic planning implementation in organizations.